On generalized finite Hankel transform - Bermúdez, Misvely (Rev. Téc. Fac. Ing. Univ. Zulia, 2011)
In this paper, a generalized finite Hankel transform is defined by using the Theory of Finite Sturm-Liouville Transform. The inversion formula and some properties are given. Additionally, it is applied to the solution of the boundary problem related to atmospheric pollution. The finite Hankel transform is obtained for a particular case.